2004
DOI: 10.1002/sia.1735
|View full text |Cite
|
Sign up to set email alerts
|

Study of the effect of different aluminium surface pretreatments on the deposition of thin non‐functional silane coatings

Abstract: This paper focuses on the effect of aluminium surface pretreatment on the formation of thin non-functional silane films. Three pretreatments were used to prepare the aluminium surface before the deposition of silane films. The generated surfaces were characterized before and after the silane film deposition by infrared spectroscopic ellipsometry (IRSE) and by the combination of SEM, AES and spectroscopic ellipsometry (SE), respectively. It is demonstrated that the amounts of hydroxyl groups at the aluminium su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
54
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 17 publications
(22 reference statements)
0
54
0
Order By: Relevance
“…The solution pH affects the molecular orientation after deposition [16,21,24]. The silane concentration is often kept low to suppress self-condensation and limit the siloxane layer thickness after deposition [16,18,19,25]. Literature generally reports that the final film thickness (linearly) increases with the solution concentration, while the uniformity decreases [25][26][27].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The solution pH affects the molecular orientation after deposition [16,21,24]. The silane concentration is often kept low to suppress self-condensation and limit the siloxane layer thickness after deposition [16,18,19,25]. Literature generally reports that the final film thickness (linearly) increases with the solution concentration, while the uniformity decreases [25][26][27].…”
Section: Introductionmentioning
confidence: 98%
“…The silane concentration is often kept low to suppress self-condensation and limit the siloxane layer thickness after deposition [16,18,19,25]. Literature generally reports that the final film thickness (linearly) increases with the solution concentration, while the uniformity decreases [25][26][27]. As a result the interfacial strength often decreases when higher silane concentrations are used [19].…”
Section: Introductionmentioning
confidence: 99%
“…This peak was assigned to the Al-O stretching of the aluminium oxide. [28] Sample Al-AAA shows a remarkably higher number of Al-A Figure 1. Fourier transform infrared spectra of the uncoated samples.…”
mentioning
confidence: 93%
“…Since silanes react with metals via their OH groups, maximizing the amount of these groups at the oxide surface is desired. In a study by Franquet et al 35 , it was shown that a pre-treatment increasing the amount of surface hydroxyls will in turn result in silane films of better uniformity and larger thickness.…”
Section: Introductionmentioning
confidence: 99%